Vietnam Task The 5th Battalion, The Royal Australian Regiment, 1966-67 - O'Neill, Robert (ANU Press, 2022)
On 24 May 1966, eight hundred men of the 5th Battalion, The Royal Australian Regiment, landed at Nui Dat, in Viet Cong territory. For the next 12 months they were faced with the task of restoring peace, civil law and regular commerce to the Vietnamese of Phuoc Tuy province. This book is a detailed record of those months in the monsoon jungles-of the problems that were faced and the solutions that were found. Captain O'Neill's position as battalion intelligence officer enabled him to view the war from the standpoint of the battalion as a whole. However, he does not omit description of personal feelings-towards the Viet Cong, the jungle environment and the Vietnamese people, as well as the other Allied forces involved in the war. Most of the book was written on the spot in Vietnam. On operations or at Battalion Headquarters, Captain O'Neill jotted down details of the war against the Viet Cong, putting the events of each day in order, often in the small hours of the following morning. Thus not only is this a factual account of the 5th Battalion's activities over the year; it is also a vivid and compelling picture of the war in Vietnam from the soldier's point of view.